BEYOND THE MYTH: Screenwriting Approaches to Biographical Films - NICHOLAS DAVIES (2023)
This PhD submission comprises an original screenplay on the relationship between African American activist Paul Robeson and the mining community of south Wales titled Robeson: They Can’t Stop Us Singing, and the accompanying exegesis. The aim is to explore, by academic study (gnosis) and creative practice (praxis), the previously overlooked field of writing biographical films, or biopics, and to acknowledge the role of the screenwriter in telling a person’s life story on film. The script is the experiment; the exegesis is the analysis and methodology. The role of the screenwriter is underrepresented across cinema studies, but no more so than in the discussion of biopics. My exegesis begins by exploring what academic and popular writing already exists on English-language biopics, highlighting that amidst auteurist approaches prevalent in cinema studies, little credit has been afforded to screenwriters. I seek to address this by examining how screenwriters have responded to historiographical and socio-political contexts while balancing the needs of the audience with factual integrity (or sometimes not), before using the case studies of Abraham Lincoln and Charles Lindbergh to explore how American hero figures have been represented on screen. How does a script written on Lincoln in 1939, for example, differ in terms of tone and political philosophy to one delivered in the 21st century? Using historical approaches, the exegesis then examines the life of Paul Robeson and the Welsh miners he knew, to observe the meticulous choices required by the screenwriter researching and writing a biopic script. Using primary sources (interviews with living dramatic writers, including the BAFTA-nominated screenwriter of the biopic, Good Vibrations) and secondary sources (screenplays, films, audio, interviews, other academic writing), I question where and when to begin and end a biographical story, which parts of a person’s life to include or jettison, how to make a historical figure’s events pertinent to a contemporary audience, and how to utilise fictionalised elements in a drama while adhering to a central truth. My own screenplay on Robeson and Wales is the embodiment of this research. The script demonstrates the myriad artistic decisions that need to be made to present the qualities and flaws of the historical figure. It shows why fictionalised moments and composite characters contribute to an understanding of a real person’s motives and feelings in a way documentary and historical writing cannot. And it stands as a record of the screenwriter’s previously overlooked contribution to creating biographical films.